Disputa política em torno do censo demográfico 2020 - Benicio, Matheus Domingos (2023)
This work presents a critical discursive analysis of the political dispute that took place around the questionnaire of the 13th Brazilian Demographic Census, carried out by the IBGE. The census dispute under scrutiny here was marked by an opacity typically associated with political processes that seek to disguise themselves as scientific elaborations. In the following pages, this opacity will be tackled so that the development of the dispute can be made comprehensible and its eminently political character can be exposed, indicating, from this, possible ways to safeguard the technical nature of the statistical work carried out by the IBGE. All this based on the discourse analysis of Ernesto Laclau and Chantal Mouffe, as well as the methodology of the Political Discourse Theory (PDT).